Comparison of the Effectiveness of Sbar and I-PASS Communication Methods in Nurse Handover: Literature Review - Khotijah Khotijah; Wastu Adi Mulyono (GLOBAL HEALTH SCIENCE GROUP, 2025)
Communication is a critical component in providing safe and high-quality nursing care. Various adverse events that occur in hospitals are mostly caused by communication errors between health workers. This literature review aims to analyze a systematic comparison of the effectiveness of the SBAR and I-PASS communication methods. Literature search methodology includes major electronic databases such as PubMed, Google Scholar with a publication time range of 2013-2023. A total of 1,008 articles were obtained from the initial search, after the screening process using the PRISMA flow diagram, 10 journals were obtained that met the criteria. Research results: Both SBAR and I-PASS methods were proven to be effective in increasing patient safety, with I-PASS showing slightly superior performance in reducing the risk of medical errors. Although both methods have a structural framework for information transfer, I-PASS shows better consistency and depth of information than SBAR. I-PASS shows superiority in handover process efficiency, with a more significant time reduction and increased communication completeness compared to SBAR. Conclusion: The I-PASS communication method is more recommended than SBAR in nursing handover practice because it has higher effectiveness in reducing the risk of medical errors and improving the quality of information transfer.